1979
DOI: 10.1159/000237836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disodium Phosphonoacetate and Iododeoxyuridine on the Multiplication of African Swine Fever Virus <i>in vitro</i>

Abstract: Disodium phosphonoacetate (PAA) was found to inhibit the replication of African swine fever virus (ASFV). The action of this compound has been compared with the inhibitory capacity of iododeoxyuridine (IDU) upon ASFV growing in Vero cells. The study was done by the immunofluorescence technique in order to detect formations of cytoplasmic virus antigens and inclusion bodies; both were found to be inhibited by IDU and PAA. At 100 µg/ml, IDU blocked completely the multiplication of ASFV and with PAA, a few scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…1 and 3-6). ASFV-inhibition by PAA and by PFA in the cultured swine MO, as reported in this study, was quite similar to the suppressive effect of PAA on ASFV-infection in the Vero-cell fibroblastoid cell line [19,33]. Moreover, the presence of CSF-1 in the MO culture medium did not alter the ASFV-inhibitory action of the two drugs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…1 and 3-6). ASFV-inhibition by PAA and by PFA in the cultured swine MO, as reported in this study, was quite similar to the suppressive effect of PAA on ASFV-infection in the Vero-cell fibroblastoid cell line [19,33]. Moreover, the presence of CSF-1 in the MO culture medium did not alter the ASFV-inhibitory action of the two drugs.…”
Section: Discussionsupporting
confidence: 85%
“…Research into the suppression of ASFV in Vero-cells did not fully address the impact of the antiviral on the host cell [19,33]. The respective concentrations ranges of PAA and PFA, needed to suppress the replication and DNA polymerase activity of ASFV (in this and other studies [19,33]), and to suppress vaccinia virus [4,21,34] were reportedly cytostatic and inhibitory for DNA polymerase ~t [4,21,36,38,46,53]. In contrast, the concentration ranges of PAA and PFA needed to inhibit the replication and DNA polymerases of the herpes viruses were on the order of one-tenth or less than that required for ASFV and vaccinia; these drug concentrations were neither cytostatic nor inhibitory for the cellular DNA polymerase a I-3, 4, 21, 36, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study megalomycin C and suramin were shown to have promising activity against ASF virus, with megalomycin C displaying the lowest MIC (4 ,uglml) and with suramin showing the lowest toxicity for cultured cells. Both compounds compared well with 5-iodo-2'-deoxyuridine or phosphonoacetic acid, which have been reported to be inhibitors of ASF virus (8,9,14). Studies in whole animals are necessary, however, to verify the potential of any of these agents against this disease.…”
Section: Resultsmentioning
confidence: 97%
“…For this reason, prospects are poor for developing a vaccine by conventional methods; therefore, attention has been concentrated on those chemical agents that are capable of inhibiting viral replication. Relatively preliminary studies have shown that phosphonoacetic acid (8,14), 5-iodo-2'-deoxyuridine (8,9), and rifampin (3) and chloroquine (7) may inhibit viral replication in vitro.…”
mentioning
confidence: 99%